Identifikasi Total Bakteri dan Keasaman Air Susu Ibu Perah (ASIP) yang disimpan di Cooler Bag - Dian Nintyasari Mustika; Siti Nurjanah; Yuliana Noor Setiawati Ulvie (Jurnal Gizi, 2019)
Exclusive breastfeeding is mother's milk given to babies up to 6 months old babies without food and drink, except drugs and vitamins. The provision of ASI in Indonesia has not been fully implemented. Efforts to improve breastfeeding behavior in mothers who have babies,especially exclusive breastfeeding, are still considered lacking. One of the things that inhibits exclusive breastfeeding is often experienced by working mothers, including insufficient knowledge and conditions for working mothers. Workers must milk breast milk during working hours if they want to give breast milk exclusively. Stored breast milk must pay attention to the temperature level and duration of storage so that the baby is safely consumed. Cooler bags are an alternative to storing breast milk if there is no refrigerator at the place where the mother works. The purpose of this study was to find out the total bacterial identification and acidity ofstored breast milk in a cooler bag. This type of research is a description with cross sectional design. The population in this study were working mothers who provided breastfeeding through breast milk. The sample in this study was breast milk from the Worker's Mother. The results were analyzed descriptively. The results showed that the treatment of slow freezing time had a significant effect on the total bacteria contained in breast milk with the result that the total bacteria in fresh breast milk showed a greater amount compared to breast milk stored in the cooler bag and pasteurized. The treatment of slow freezing time has a significant effect on the acidity of breast milk with the result that on day 0, fresh breast milk shows that the average range of breast milk pH ranges from pH 7.1 to 7.5 while on day 1 fresh milk showed that the average pH range of breast milk ranged from pH 5.5 to 6.6. ASI stored in cooler bags on day 0 the average pHrange of breast milk ranged from pH 5.5 to 5.9, whereas on day 1 the average pH range of breast milk ranged from pH 5.9 to 6.6 . Whereas in breast milk pasteurized on day 0 the average range of breast milk pH ranged from pH 7.1 to 7.7, whereas on day 1 the average pH range ofASI ranged from pH 5.9 to 6.7.Keywords: stored breast milk, total bacteri, pH